The Effect of Product Development and Product Quality on Consumer Satisfaction at PT. Langgeng Perkasa in Cikarang - Iyus Rustandi (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to determine the effect of product development and product quality on consumer satisfaction at PT. Langgeng Perkasa in Cikarang. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The result of this research is that product development has a significant effect on customer satisfaction by 45.2%, hypothesis testing is obtained t count > t table or (8.809 > 1.986). Product quality significantly affects consumer satisfaction by 41.4%; hypothesis testing is obtained t count > t table or (8,153 > 1,986). Product development and product quality simultaneously significantly affect consumer satisfaction with the regression equation Y = 10.689 + 0.393X1 + 0.345X2. The contribution of influence is 52.1%.